2015
DOI: 10.3390/nu7115474
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Exposure to Nutrition and Health Claims on Pre-Packed Foods: Use of Sales Weighting for Assessing the Food Supply in Slovenia

Abstract: Insights into the use of health-related information on foods are important for planning studies about the effects of such information on the consumer’s understanding, purchasing, and consumption of foods, and also support further food policy decisions. We tested the use of sales data for weighting consumers’ exposure to health-related labeling information in the Slovenian food supply. Food labeling data were collected from 6342 pre-packed foods available in four different food stores in Slovenia. Consumers’ ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 37 publications
5
51
2
2
Order By: Relevance
“…However, this research is in line with results from studies in other countries that showed disease risk reduction claims were only present on 1-3% of food labels [3,5,50]. Nevertheless, another 6 disease risk reduction claims were approved between 2014 and 2016 (after data collection for this study) [51][52][53][54][55][56], which may result in an increase in their use by food manufacturers, although research has shown that disease risk reduction claims are not often used on food labels [5].…”
Section: Discussionsupporting
confidence: 90%
“…However, this research is in line with results from studies in other countries that showed disease risk reduction claims were only present on 1-3% of food labels [3,5,50]. Nevertheless, another 6 disease risk reduction claims were approved between 2014 and 2016 (after data collection for this study) [51][52][53][54][55][56], which may result in an increase in their use by food manufacturers, although research has shown that disease risk reduction claims are not often used on food labels [5].…”
Section: Discussionsupporting
confidence: 90%
“…To determine the presence of NC and HC and the rest of yoghurt attributes, we created a database that collects information regarding yoghurt products available between July and September 2015. The creation of the database was based on the standardized protocols established by the International Network for Food and Obesity Research, Monitoring and Action Supporting the (INFORMAS) of Rayner et al (2013) and Pravst & Kušar (2015). The final sample included yogurts that contained one nutritional and/or health claim in the package and were in accordance to the official EU definitions 4 .…”
Section: Data Collectionmentioning
confidence: 99%
“…The database was created in Microsoft Excel 2010 that allowed the collection of the following information: Name of the distribution chain, product category, product name, brand, price, presence or absence of NCs, and the HCs (if any). This study only includes nutritional statements expressed in text and not as symbols unlike the study of Pravst & Kušar (2015).…”
Section: Data Collectionmentioning
confidence: 99%
“…1924/2006. Nevertheless, the symbol can still be found on about 2% of prepacked products in the food supply (Hieke et al, 2016;Pravst & Kusar, 2015).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%